Living with the neighbors: the effect of Venezuelan forced migration on wages in Colombia - Peñaloza Pacheco, Leonardo (2019)
The aim of this paper is to estimate the causal effect of the migration of Venezuelans to Colombia on the Colombian real wage, since 2016. In the second semester of 2016, the borders between Colombia and Venezuela were reopened after a year of being closed due to a political crisis between the two countries; this re-opening is exploited as an identification strategy. Using data from the Unidad Administrativa Especial de Migración Colombia and the Registro Administrativo de Migrantes Venezolanos in Colombia, it is estimated that the migratory flow of Venezuelans to Colombia increased the Economically Active Population of the border areas of La Guajira and Norte de Santander by approximately 10% and 15%, since its reopening. Differences-in-differences methodology and Synthetic Control Method are implemented and the results show that the increase in labor supply in these regions that resulted from the migratory flow generated a decline in real hourly wages of approximately 6%-9% on average. This decrease in real wages appears to be greater for men as compared to women. There is also evidence of a greater drop in real wages among people with lower levels of qualification and in conditions of informal employment.